Harvesting target positioning and robotic arm obstacle avoidance algorithm based on improved YOLOv8 and BIT* - Xu, Yingwu (Frontiers in Mechanical Engineering, 2026)
IntroductionTo address the core challenges of inaccurate fruit occlusion localization and inefficient robotic arm dynamic obstacle avoidance in complex, unstructured agricultural environments, this study proposes an integrated algorithm for harvesting.MethodsThe proposed algorithm is built upon an improved YOLOv8 model and the BIT* planner. The YOLOv8 model was enhanced by introducing the Swin Transformer module to improve multi-scale feature fusion and global context modeling. The BIT* planner was integrated with a BiLSTM network to endow it with dynamic obstacle prediction capabilities, thereby constructing a unified architecture for visual perception and motion planning.ResultsExperimental results demonstrated that the algorithm achieved real-time performance with a processing frame rate of 32.7 fps and an inference time of 32.6 ms for target localization, with a localization error standard deviation as low as 1.70 mm. In obstacle avoidance planning, it achieved a balance with manipulator energy consumption of 124.58 J, while controlling the computational load and memory resource consumption per task to 22.7 GFlops and 187 MB, respectively.DiscussionThis approach provides a high-precision, low-energy-consumption cooperative control solution for agricultural harvesting robots, advancing the practical application of automated fruit and vegetable harvesting.